A -t végű igék kijelentő módja mint egyetemes változó? - Csernicskó István; Черничко Степан; Csernicsko Istvan (Argumentum Kiadó, 2002)
A tanulmány első tanulsága arra mutat rá, hogy a Kárpát-medence magyarsága körében országhatároktól függetlenül működik a differenciált stigmatizáció a suksükölést és a szukszükölést illetően. A második következtetés kutatásmódszertani szempontból lényeges: bármilyen kérdőíves vizsgálat megtervezésekor figyelembe kell venni, hogy a feladatok típusa hatással van az eredményekre, ezért minden jelenséget lehetőség szerint többféle feladattal kell vizsgálni, az eltérő feladattípusokból nyert adatokat pedig nem szabad összevontan kezelni. A harmadik tanulság az anyanyelvi oktatás szempontjából érdemes figyelemre: aki suksökül, az nagy valószínűséggel szukszüköl is, de ez fordítva csak ritkán igaz; ez azt jelenti, hogy az iskolai oktatás során külön figyelmet kell fordítani a-t és -szt végű igék kijelentő módjára.

Abstract. In the spring of 1988, the Hungarian Public Opinion Research Institute and the Linguistics Institute of the Hungarian Academy of Sciences conducted a questionnaire test about selected s-sues of language use involving a 850-member representative sample of the over-18 population of Hungary. A comparable study in 1996 explored the language use of Hungarians living in neighbouring countries as well as those living in Hungary. The author's own data collection and analysis of the language of Hungarians in Subcarpathia (Ukraine) was subsequently conducted in a similar manner. The present paper seeks to find out it, and to what extent, substandard grammatical homonymy in indicative vs. imperative forms of l-final verbs can be seen as a regional phenomenon or if it is characteristic of the Carpathian Basin as a whole. The main conclusion of this sociolinguistic study is that the occurrence and use of such homonyms, going back to the popular speech of earlier centuries, exhibit a similar tendency throughout the Carpathian Basin as concerns its broad outlines, although the detailed results are also influenced by the character of the individual tasks that were presented to the subjects.
Indicative forms of t-final verbs as a universal variable?
https://epa.oszk.hu/00000/00032/00014/pdf/EPA_00032_magyar_nyelv_2002_03_CSERNIS.pdf
Keywords: -t végű igék; egyetemes változó; kijelentő mód